Complement biomarkers reflect the pathological status of neuromyelitis optica spectrum disorders - Miyamoto, Katsuichi; Minamino, Mai; Kuwahara, Motoi; Tsujimoto, Hiroshi; Ohtani, Katsuki; Wakamiya, Nobutaka; Katayama, Kei-ichi; Inoue, Norimitsu; Ito, Hidefumi (Frontiers in Immunology, 2023)
Complement is involved in the pathogenesis of neuroimmune disease, but the detailed pathological roles of the complement pathway remain incompletely understood. Recently, eculizumab, a humanized anti-C5 monoclonal antibody, has been clinically applied against neuroimmune diseases such as myasthenia gravis and neuromyelitis optica spectrum disorders (NMOSD). Clinical application of eculizumab is also being investigated for another neuroimmune disease, Guillain-Barré syndrome (GBS). However, while the effectiveness of eculizumab for NMOSD is extremely high in many cases, there are some cases of myasthenia gravis and GBS in which eculizumab has little or no efficacy. Development of effective biomarkers that reflect complement activation in these diseases is therefore important. To identify biomarkers that could predict disease status, we retrospectively analyzed serum levels of complement factors in 21 patients with NMOSD and 25 patients with GBS. Ba, an activation marker of the alternative complement pathway, was elevated in the acute phases of both NMOSD and GBS. Meanwhile, sC5b-9, an activation marker generated by the terminal complement pathway, was elevated in NMOSD but not in GBS. Complement factor H (CFH), a complement regulatory factor, was decreased in the acute phase as well as in the remission phase of NMOSD, but not in any phases of GBS. Together, these findings suggest that complement biomarkers, such as Ba, sC5b-9 and CFH in peripheral blood, have potential utility in understanding the pathological status of NMOSD.